PENINGKATAN KUNJUNGAN WISATAWAN NUSANTARA KE AIR TERJUN DLUNDUNG, MOJOKERTO MELALUI STRATEGI PROMOSI DIGITAL - Khotimah, Miftakul Nurun; Kusuma Negara, I Made; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p21, 2023)
The Dlundung Waterfall Perhutani area is one of the leading destinations in Mojokerto Regency which offers unique natural tourist views such as waterfalls and visiting tourists can do several tourist attractions such as camping, swimming, playing in the rabbit house rides or enjoying waterfall views in a cafe with waterfall views. The attractiveness of the Dlundung Waterfall tour can attract domestic and foreign tourists to visit which is offset by promotion through social media which can increase the engagement of this destination. The purpose of this research is to find out the promotion mix in the Dlundung Waterfall Perhutani area. The method used is a SWOT analysis of the internal environment and the external environment for tourist destinations in the Dlundung Waterfall Perhutani Region by utilizing the results of observations, interviews, questionnaires which were distributed to 80 respondents using the closed method. The informant determination technique used in this study is the purpose strategy. The results of this study, based on SWOT analysis of the internal and external environment of the Dlundung Waterfall Perhutani Area, show that this destination is in quadrant I of an aggressive strategy. This quadrant states that the Dlundung Waterfall Forestry Area can carry out several strategies to carry out market development and collaboration with third parties for the development of the destination itself.